Changes in biochemical parameters in horses during 40 km and 80 km endurance races - Klobučar Karla (Sciendo, 2019)
During intensive physical activity horses are exposed to thermolysis, electrolyte loss and rising amounts of catabolic products, which results in alterations of biochemical blood parameters due to the horse’s adaptation to metabolic stress. The aim of the present study was to determine the effect of intensive physical activity on serum biochemical parameters in horses competing in 40 and 80 km endurance races. Blood samples were taken from 28 horses before and after the race over four competitions, with a total of 53 samples analyzed. Biochemical parameters studied included creatine kinase, lactate dehydrogenase, aspartate aminotransferase, urea, creatinine, gamma-glutamyl transferase, glucose, triglycerides, cholesterol, sodium, potassium, calcium and magnesium. The extent of change in pre- and post-race values was compared between categories of age, gender, breed, distance and average speed of horses. Creatine kinase and blood glucose values prior to the race were higher than the reference values. Values of renal parameters and parameters of muscle damage increased after the races, and the degree of change was more pronounced at longer racing lengths, as well as at lower average speed. Electrolyte loss was more prominent during longer races. This study demonstrated that endurance races cause evident changes in serum electrolyte concentrations, renal parameters and markers of muscle damage in horses. These changes are observable in horses at both short and long duration endurance races.